United Nations Peacekeeping: Reevaluating Sexual Exploitation and Abuse by UN Peacekeepers - Kimura, Chisato (My University, 2022)
In 2004, UN Peacekeepers were deployed to Haiti to protect civilians and bring stability to the region. Reports from the United Nations Stabilizing Mission in Haiti, however, tell a story of exploitation, abuse, and egregious harm to civilians – including children – by the very peacekeepers deployed to protect and serve them. Over 130 UN Peacekeepers exploited children in Haiti between 2004 and 2007, and although 117 were sent home, none were ever criminally prosecuted. The case in Haiti is unfortunately not an anomaly. SEA has been reported in every peacekeeping mission over the last 30 years, including in all fourteen active missions where UN peacekeepers are currently deployed. UN Peacekeeping missions are deployed in conflict and crisis zones, with explicit mandates to protect civilians from harm and violence. Yet, UN peacekeepers are often perpetrators of violence themselves, in the form of sexual exploitation and abuse (SEA). The UN has taken multiple approaches to address the perpetration of SEA by UN peacekeepers, but SEA continues to be a major problem and there has been little accountability for both individuals and institutions involved in perpetrating SEA. SEA is harmful to the survivors and communities where it is perpetrated, and it de-legitimizes the UN’s humanitarian mission and mandates to protect civilians. The continued perpetration of SEA by UN peacekeepers across time and place merits the question of why SEA continues to persist, and what are the factors and conditions contributing to an environment where SEA is perpetrated with little accountability? This project examines the previously under-studied structural conditions contributing to UN peacekeeper-perpetrated SEA on several levels: host states and troop-contributing countries (TCCs), international financial institutions and the United Nations, and capitalist, neo-colonial, and patriarchal world systems. By using data analysis and case examples, my study is an attempt to analyze the role of laws, financial agreements, and institutions, all situated within a global capitalist system, in perpetuating gender, race, and class-based discrimination and violence, which in turn allows SEA to continue being perpetrated by UN peacekeepers. UN peacekeeping operates within a context of neoliberal power and capital that reflect older and persistent traditions of colonialism and patriarchy. Starting with this understanding, I present my argument that SEA perpetrated by UN peacekeepers is a manifestation of gender-based violence intrinsic to capitalist, neo-colonial, and patriarchal institutions, laws, and financial policies and that critically analyzing these systems is a prerequisite to effectively eradicating UN peacekeeper-perpetrated SEA.
Keywords: United Nations; United Nations Peacekeeping; Peacekeeping; Gender Based Violence (GBV); Sexual Exploitation and Abuse; International Financial Institutions; International Monetary Fund; World Bank; Sexual Violence; Women's Rights; International Institutions; Capitalism; Critical Theory; Post-Colonialism